The Influence of Online Shopping Transactions and Consumer Trust on Consumer Satisfaction of E-Commerce TikTok Shop: A Case Study on Students of the Faculty of Economics and Business, University of Mataram - Intan Dwi Saputri M; Hilmiati, Hilmiati (Future Techno-Science, 2026)
This study aims to examine the Influence of Online Shopping Transactions and Consumer Trust on Consumer Satisfaction of Tiktok Shop E-Commerce: Case Study of Students of the Faculty of Economics and Business, University of Mataram. This research is a quantitative study. The population in this study were all students of the Faculty of Economics and Business, University of Mataram who had made purchases through TikTok Shop, with an unknown population size. The research sample was 100 respondents determined using the Bernoulli formula. Data collection was carried out through the distribution of online questionnaires (Google Form). The dependent variable in this study was Consumer Satisfaction, while the independent variables consisted of Online Shopping Transactions and Consumer Trust. Data analysis was carried out using the multiple linear regression method. The results showed that Online Shopping Transactions and Consumer Trust had a positive and significant effect on Consumer Satisfaction of Tiktok Shop E-Commerce among Students of the Faculty of Economics and Business, University of Mataram. The Online Shopping Transactions and Consumer Trust factors had an influence of 66.3% on Consumer Satisfaction, while the remaining 33.7% was influenced by other factors not examined in this study.